Computer-aided automated flow chemical synthesis of polymers - Li Yu; Baiyang Chen; Ziying Li; Yue Su; Xuesong Jiang; Zeguang Han; Yongfeng Zhou; Deyue Yan; Xinyuan Zhu; Ruijiao Dong (Giant, 2024)
Synthetic chemistry has played a vital role in miscellaneous fields of human civilization over the past century. The synthetic stage yet remains time-consuming and labor-intensive. To overcome these limitations, automation has been introduced to transform synthetic chemistry, leading to the development of high-throughput methods for molecular discovery. Automated flow chemical synthesis (AFCS) has recently emerged as a promising candidate, offering improved efficiency, scalability, and sustainability over the well-known automated solid-phase peptide synthesis. To further advance AFCS, elements like artificial intelligence-based computer-aided structure design and synthesis planning, autonomously assembled compatible synthesis with enhanced automated process control, and autonomous optimization can be considered. This review focuses on recent advances in computer-aided automated flow chemical synthesis (CAAFCS) of polymers in living polymerization and iterative synthesis strategy. The current challenges and outlook are finally discussed for developing more powerful CAAFCS systems and expanding their applicability across numerous fields, potentially providing brand-new perspectives and guidelines for future developments in this field.